Executive Committee Minutes 2018-04-26 - Academic Senate:::::::::
Agenda – Approved. 4/12/18 – Approved. Chair Report. President Report. Provost Report. From EPC: Expedited Proposal – Hutchins – approved for the Senate consent calendar. From EPC: Revision to the Syllabus Policy (formerly Course Outline Policy) – approved for the Senate agenda. From EPC: Temporary 48 unit GE pattern – approved for the Senate agenda. Vice President of Student Affairs Report. Discussion of LMS presentation to the Senate. APARC Priority Recommendations – approved for the Senate agenda. EPC Report. Associated Students Report. Senate Agenda – approved.